Accurate dosimetric measurement of large extended SSD fields for comparison to TPS models. (April 2021) - Duncan-Gelder, Phillip; Moggré, Alicia; Cousins, Andrew; Wilder, Benjamin; Marsh, Steven
Highlights: Accurate measurement of extended source-to-surface distance fields is time consuming. A device was made to accurately and quickly measure large profiles. Treatment Planning System modelling with Monaco was performed. Comparisons to Monaco collapsed cone algorithm agreed well for block phantoms. Feasibility established to investigate planning system agreement for patients. Abstract: Purpose: There is little evidence in the literature which quantifies the accuracy of Treatment Planning Systems (TPSs) using large fields at extended SSD (eSSD). This paper introduces the approach taken at Christchurch Hospital, New Zealand to validate the use of the Monaco TPS for Total Body Irradiation (TBI) treatments. Methods: A purpose-built device for allowing precise movements of block-like phantoms called a Phantom Mobility Device (PMD) was used for collecting measurements at eSSD. These measurements were used for determining the ability of the Monaco TPS (originally validated for SSDs between 80 and 110 cm) to accurately model dose distributions for TBI treatments at Christchurch Hospital on either treatment machine one (T1) or two (T2) with SSD values of 341 and 432.6 and clinically useful field sizes of 120 and 170 cm, respectively. Results: We found that within the limits of measurement uncertainty the PMD contributed no determinable scatter to the measurements and proved a reliable approach for eSSD dose measurements. Additionally, by applying depth and off-axis distance constraints of use for TPS information it is possible to use the existing Monaco CCC model at eSSD for block phantom geometries. Dose Difference (DD) analysis showed a clinically acceptable agreement between the CCC model and measured data over a range of depths and off-axis distances. Conclusions: The PMD was determined to be a useful tool for accurate measurement of extended SSD treatment fields. Monaco TPS CCC model agreed well for block phantoms so future comparisons to anthropomorphic phantoms or patient data are feasible.